Inflammation and Retinal Disease: Complement Biology and Pathology - Lambris, John D.; Lambris, John D.; Adamis, Anthony P.; Adamis, Anthony P. (Advances in Experimental Medicine and Biology, 2010)
Numerous studies have pointed to the key role of complement in the pathogenesis of retinal disease, particularly age-related macular degeneration (AMD). Reports about new gene associations and links to other physiological pathways are emerging almost on a weekly base. Several promising clinical candidates covering a wide area of potential treatment applications are in the pipelines of both industrial and academic groups. This indicates an increasing interest in complement as a therapeutic target. In view of these exciting discoveries, scientists from around the world convened at the 1st Aegean Conferences Conference on Inflammation and Retinal Disease: Complement Biology and Pathology (June 10-17, 2007) in Crete, Greece, to discuss recent advances in this rapidly-evolving field. This volume represents a collection of topics on the functions of complement in eye diseases, pathophysiology, protein structures, and complement therapeutics discussed during the conference.